After a stroke : 300 tips for making life easier - Hutton, Cleo, 1949- (Demos, 2005)
The American Stroke Association estimates that about 4,800,000 stroke survivors are alive today and about 700,000 people suffer a new or recurrent stroke each year. After a Stroke: 300 Tips for Making Life Easier is addressed to this wide audience. Because hospital stays after a stroke are often short compared to the lengthy period of rehabilitation and gradual return of function, After a Stroke concentrates on the home recovery process after a stroke and assists those patients and their families in attempting to grow from patient back to person. The author, a twelve-year stroke survivor and n.